Phage-based biocontrol of Salmonella and E. coli in raw chicken filets: optimizing phage-based solutions to enhance food safety under cooled storing conditions - Berhilevych, Oleksandra; Peh, Elisa; Vahle, Johanna Charlotte; Plötz, Madeleine; Kittler, Sophie (Frontiers in Microbiology, 2026)
Food safety continues to be an important issue for consumer protection and public health globally. Chicken meat is considered a primary source of Salmonella and E. coli infections in humans. In recent years, phage-based biocontrol has attracted attention as a promising approach to combat these foodborne pathogens due to its advantages over traditional methods and its biological properties as a natural bactericide. Using phage-based control as a decontamination method to ensure microbial safety of food aligns with the One Health strategy for sustainable pathogen control and prevention of foodborne infections. This study aimed to develop and evaluate the effectiveness of a three-phage cocktail with optimized efficacy for simultaneously controlling Salmonella and E. coli on raw chicken filets during cold storage. To optimize the efficacy of the final phage cocktail, three phages were selected according to their host ranges and the efficiency of plating (EOP) values. They were combined in a cocktail, and the host range was expanded using the Appelmans protocol for 30 training cycles. The antibacterial efficacy of the trained three-phage cocktail was evaluated in liquid culture using a planktonic killing assay (PKA) and on raw chicken filets stored at 4 ± 0.5 °C for 72 h, employing multiplicities of infection (MOI) of 1, 10, and 100 for targeting filets contaminated with single Salmonella and E. coli strains and a mixture of both. After training according to the Appelmans protocol, the cocktail showed an expanded host range, covering 62.5% (5/8 after 30 training cycles) instead of 37.5% (3/8 before training) of the tested bacteria. The planktonic killing assay demonstrated that the trained three-phage cocktail had a significant inhibitory effect on bacterial growth of the Salmonella strains (4/4, 100%) from 3 to 6 h, while the non-trained initial three-phage cocktail’s effect was less pronounced (1/4, 25%) and lasted only 3 h. However, three of four E. coli strains (75%) were not sensitive to the three-phage cocktail after 30 cycles of the Appelmans protocol compared to two out of four strains (50%) with the non-trained initial three-phage cocktail. On raw chicken filets, significant bacterial reduction was observed when using MOI 10 and 100 of the trained three-phage cocktail. A maximum reduction of 1.56 log10 CFU/mL of Salmonella BfR 20-SA00418 and 1.48 log10 CFU/mL of E. coli 19/302/1/A after 72 h compared to placebo-treated controls were achieved using an MOI of 100. We observed a synergistic effect of the three-phage cocktail compared to single treatment, with a stronger effect on Salmonella than on E. coli strains. Using the Appelmans protocol improved the effects of the developed three-phage cocktail, leading to broader pathogen coverage. The efficacy of the developed three-phage cocktail under cold storage conditions and its ability to reduce the bacterial load in raw chicken filets highlighted its potential for extending shelf life and reducing risks for the consumer. The findings of this study demonstrate that the developed and optimized three-phage cocktail is a promising biocontrol agent for enhancing safety in raw chicken meat production.